EFEK MEREK DOMESTIK VS ASING DAN INFORMASI COUNTRY-OFORIGIN TERHADAP PERSEPSI DAN SIKAP KONSUMEN : STUDI PERILAKU KONSUMEN PADA PRODUK SUSU OLAHAN - Suci Paramitasari Syahlani (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
The aims of this research is to identify the effect of domestic and foreign branding towards consumer perceptions and attitudes, also country-of-origin (COO) information towards consumer attitudes. Product stimuli used in this research was processed milk product. This research was held by factorial design and paper and pencil experiments are used as experiment tool. Eighty (80) males and 80 females of Gadjah Mada University students are used as respondent and then classified into four experiment groups which were domestic branding-domestic COO, domestic branding-foreign COO, foreign branding domestic COO and Foreign brandingforeign COO. The analysis method employed in the study was independent sample t-test dan regression analysis. The results indicated that effect of foreign branding, which was English branding, showed its positive effect better on consumer perceptions and attitudes of processed milk product. Consumer perception showed that foreign branded processed milk product had higher quality than domestic branded processed product. Positive attitudes consumer toward foreign branded processed milk product was higher than domestic branded processed milk product. Foreign COO showed higher positive consumer attitudes than domestic COO. Gender factor did not show its effect on consumer attitudes toward processed milk product’s brand. This research also showed that effect of foreign branding was higher than COO information on product evaluation.